Cystatin C in risk prediction after transcatheter aortic valve replacement: a retrospective analysis. (6th June 2022) - Kuwabara, Kensuke; Zen, Kan; Yashige, Masaki; Takamatsu, Kazuaki; Ito, Nobuyasu; Kadoya, Yoshito; Yamano, Michiyo; Yamano, Tetsuhiro; Nakamura, Takeshi; Yaku, Hitoshi; Matoba, Satoaki
Abstract: Aims: No study has evaluated the prognostic value of the chronic kidney disease (CKD) classification by cystatin C‐based estimated glomerular filtration rate (eGFR) (CKDCys classification) in patients undergoing transcatheter aortic valve replacement (TAVR). This study aimed to compare the prognostic value of CKDCys classification and CKD classification by creatinine‐based eGFR (CKDCr classification) in risk prediction after TAVR. Methods and results: We retrospectively analysed consecutive 219 patients with symptomatic severe aortic stenosis who underwent TAVR at our institute between December 2016 and June 2019. Pre‐operative CKDCr and CKDCys classifications were evaluated for their prognostic value of 2‐year major adverse cardiovascular and cerebrovascular events (MACCE) after TAVR. MACCE was defined as the composite of all‐cause mortality, non‐fatal myocardial infarction, stroke, and rehospitalization for worsening congestive heart failure. Participants had a median age of 86.0 years and were predominantly female (76.9%). In 96.6% of the cases, TAVR was performed using transfemoral access. The median creatinine‐based eGFR (52.85 mL/min/1.73 m 2 ) was higher than the cystatin C‐based eGFR (41.50 mL/min/1.73 m 2 ). Downward reclassification in CKD stages based on eGFRCys was observed in 49.0% of patients. During a median follow‐up period of 575.5 (interquartile range: 367.0–730.0) days, 58 patients presented with MACCE. CKDCys classification, but not CKDCr classification, significantly stratified the risk of 2‐year MACCE in patients after TAVR by log‐rank test ( P = 0.003). In multivariate Cox regression analysis, only CKDCys stage 3b [hazard ratio (HR) = 4.37; 95% confidence interval (CI): 1.28–14.91; P = 0.019] and CKDCys stage 4 + 5 (HR = 3.72; 95% CI: 1.06–12.99; P = 0.040) were significant predictors of MACCE after adjustment for potential confounders. Conclusions: The CKDCys classification could better assess the risk than the CKDCr classification in patients undergoing TAVR. CKDCys stage 3b and stage 4 + 5 correlated with adverse outcomes.